Therapeutic Metaphors Enhance Memory Systems in Mental Health Contexts - Fei Yu; Zhijie Zhang; Wencai Zhang (Brain and Behavior)
ABSTRACT Background Psychotherapeutic memory plays an important role in maintaining therapeutic effects; however, the neural mechanisms of therapeutic metaphor promoting long‐term memory were still unknown. Objective This study used metaphorical micro‐counseling dialog scenarios to investigate the memory effect of therapeutic metaphor and correlated neural mechanisms. Methods At first, 31 participants read a mental distress problem, followed by a metaphorical or a literal solution, while undergoing functional magnetic resonance imaging scanning during the encoding phase. One week later, a recognition memory test was performed outside the scanner. Results The results revealed that metaphorical solutions were associated with higher insight experiences and better memory performance than literal solutions. Greater activations were observed in the multiple memory systems, including episodic (parahippocampal gyrus, hippocampus, and thalamus), emotional (amygdala), and procedural/implicit (caudate, putamen, and cerebellum), in contrast to later remembered versus later forgotten based on the gap between metaphorical and literal solutions. Insightfulness and activities of the hippocampus, caudate, and cerebellum could predict memory performance. Conclusions These findings indicated that multiple memory systems are involved in successful memory encoding of therapeutic metaphors; this suggested that incorporating metaphors into psychotherapy practices could lead to better retention of therapeutic information and improve clinical outcomes compared to literal psychotherapy.